The Living Qur’an in the Manaqiban Tradition: Qur'anic Reception and Religious Meaning among the Haurendeng Community - Abdul Halim; Insan Kamil; Mushallina Hilma (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This article examines the phenomenon of the living Qur’an in the manaqiban tradition practiced by the Haurendeng community, West Java. The Qur’an is understood not only as a sacred text to be read and interpreted, but also as a living reality that appears in the various religious practices and social experiences of Muslim communities. This study aims to analyze how Qur’anic verses are received, practiced, and given meaning within the manaqiban tradition, and how the community constructs religious meanings through this practice. This research employs a qualitative approach using the living Qur’an perspective and reception studies. Data were collected through observation, interviews, and documentation related to the implementation of manaqiban rituals in the Haurendeng community. The data were analyzed using Peter L. Berger and Thomas Luckmann’s theory of social construction and Karl Mannheim’s theory of meaning, consisting of objective meaning, expressive meaning, and documentary meaning. The findings show that manaqiban functions as a form of Qur’anic reception in which Qur’anic verses are not merely recited as ritual texts but are understood as sources of spiritual values, blessings, and guidance in everyday life. The community interprets manaqiban as a medium for strengthening faith, maintaining social relationships, and expressing religious identity. This study demonstrates that the living Qur’an reflects the dynamic relationship between Qur’anic texts, local traditions, and community religious experiences).